PENGARUH KOMITMEN ORGANISASI, LOCUS OF CONTROL DAN TEKANAN ANGGARAN WAKTU AUDIT PADA PENERIMAAN UNDERREPORTING OF TIME - Limawan, Yenni Fransisca; Harta Mimba, Ni Putu Sri (E-Jurnal Akuntansi, 2016)
This study aimed to determine the effect of KAP organizational commitment, external locus of control and audit time budget pressure on the behavior of underreporting of time. The population in this study consisted of all auditors in KAP Bali based on Public Accounting Firm and Certified Public Accountants directory issued by the Indonesian Institute of Certified Public Accountants (IAPI) in 2015  amounts to 9 public accounting firm. Based on the sampling saturated in the selection of the sample, total number of samples was 55 auditors. The data used was primary data collected by questionnaire method. The data analysis technique used in this study is multiple regression analysis. Based on the analysis showed that the KAP organizational commitment had significant negative effect on the behavior of underreporting of time. External locus of control and audit time budget pressure variables had significant positive effect on the behavior of underreporting of time.
Keywords: KAP organizational commitment, external locus of control, audit time budget pressure, underreporting of time